Design and Construction of A Grid Antenna to Enhance Global System for Mobile Communications 900 Mhz Signal Reception - Ayu Widiyastuti; Ramiati Ramiati; Agus Purwadi; Rini Febriani Rini Febriani (Politeknik Negeri Padang, 2024)
Human life is inseparable from the interaction between humans as social beings and technology as the medium used by humans. The capabilities of technology have addressed various human challenges for interacting with each other, where limitations of distance, time, and space are no longer barriers to human desire for communication. The Global System for Mobile communication (GSM) is a cellular communication technology applied to mobile communication, especially mobile phones, thus providing conveniences as a medium for information delivery. However, in remote or rural areas far from the Base Transceiver Station (BTS), the signal coverage is poor. This will disrupt communication such as short message service (SMS), telephone calls, internet access, and other forms of communication. An antenna is a device used to transmit or receive electromagnetic waves. Reception using an antenna will amplify the signal acquisition according to the antenna's capabilities. GSM (Global System for Mobile Communications) service providers, with their limited network coverage, create a significant need for signal acquisition enhancement. The Grid antenna is one of the options for signal acquisition enhancement. The Grid antenna has two main components: the driven element, which is a dipole, and a reflector that serves to reflect the signal transmission. This Final Project is designed, realized, and measured on a grid antenna at GSM 900 MHz. This antenna is intended to serve as a supporting medium to enhance GSM signal reception in order to maximize signal acquisition and connection.